The Preconception Diet and Folic Acid Intake in a Post-Conflict Setting: Insights from Private Clinics in Benghazi, Libya. - El Mogassabi, Abeir; S. Saad, Salima; Khaled, Ibtissem; Bin Quweerish, Nourhan; Sati, Efaf; Saeid, Maha; Salem, Fatima; Atia, Sofian (Benghazi University Medical Journal, 2025)
Background: Maternal nutrition during the preconception period is crucial for fetal development and pregnancy outcomes. Aim: This study aims to assess the dietary intake and folic acid (FA) consumption among pregnant women in Benghazi, Libya, following eight years of political instability. Method: A cross-sectional study was conducted with 74 first-trimester pregnant women attending private antenatal clinics between February and June 2019. Dietary intake was evaluated using the European Prospective Investigation into Cancer and Nutrition Food Frequency Questionnaire (EPIC-FFQ), adapted for the Libyan population, and analyzed using the food frequency questionnaire European prospective investigation into cancer and nutrition tool for analysis (FETA). Results: The analysis revealed diets high in energy but deficient in essential nutrients. Only 26% of women-initiated FA supplementation before pregnancy, while 16% did not consume FA at all. The mean fiber intake 15.05 g/day was significantly lower than recommended p < 0.001. Micronutrient deficiencies were observed in iron and folate, while vitamin A intake was excessive. Additionally, 43% of participants were overweight or obese before pregnancy. Socioeconomic factors, including low employment rates 30% and limited household income 54% ≤1000 Libyan Dinar/month, likely contributed to these nutritional challenges. Conclusion: Pregnant women in Benghazi exhibit dietary inadequacies, particularly low fiber, iron, and folate intake, and insufficient pre-conceptional folic acid use, highlighting nutritional vulnerabilities in this conflict-affected area.